The Seven pillars of health - Colbert, Don. (Lake Mary, Fla. : Siloam, 2007)
Discusses the importance of seven principles in correcting poor health, explaining the body's need for water, rest, living food, exercise, detoxification, dietary supplements, and stress management.
1. Water -- 2. Sleep and rest -- 3. Living food -- 4. Exercise -- 5. Detoxification -- 6. Nutritional supplements -- 7. Coping with stress.
Includes bibliographical references and index.
Keywords: Christianity; Health Behavior; Religion and Medicine; Self Care; Self-care, Health; Health; Health -- Religious aspects -- Christianity